Pengenalan Sistem Distribusi Air Bersih di Bandara - Kurniawati, Zulina; Kurnianto, Benny; Ismail, KGS. M.; Arnas, Yenni; Fatra, Oka; W., Imam Hariyadi (Jurnal Pengabdian Kepada Masyarakat, 2024)
The inadequate information among high school students towards the airport mechanical engineering (TMB) has urged the need to publicize TMB more extensively. One of the endeavors is to conduct activities introducing the clean water distribution system at the airport as an implementation of one of the competencies of the TMB, namely the Water Pumping System. The purpose of this activity is not only to attract the interest of participants to continue their education at PPI Curug, especially in the TMB but also to provide basic knowledge about clean water distribution. This activity was attended by students from SMK Penerbangan Dirgantara along with companion teachers. The activity was conducted using two methods: delivering the material in the classroom, followed by practical exercises in the Water Pumping System laboratory. The participants were then evaluated during working on a simulation project of clean water distribution. Through this community service activity, participants gained not only knowledge and information about the TMB and its competencies but also acquired knowledge and skills related to the clean water distribution system. They had the opportunity to directly practice and experience the clean water distribution system and the piping system.